223k views
5 votes
Math Nation, please help asap ------------------> NO LINKS PLEASE

Let f(x)=2x^2+3 and g(x)=-x^2+6x+2. which statements below are true for f(x)*g(x)? Select all that apply.

Math Nation, please help asap ------------------> NO LINKS PLEASE Let f(x)=2x^2+3 and-example-1

1 Answer

3 votes

Answer

Constant term is 6

The x^3 has the coefficient of 12

The resulting ploynomial has a degree of 4

Explanation

Given the functions

f(x)=2x^2+3 and g(x)=-x^2+6x+2.

f(x)*g(x) = (2x²+3)(-x²+6x+2)

Take the product

f(x)*g(x) = (2x²+3)(-x²+6x+2)

f(x)*g(x) = -2x^4+12x^3+4x^2-3x^2+18x+6

f(x)*g(x) = -2x^4+12x^3 +x^2 + 18x+6

This shows that the leading term is -2x^4

Constant term is 6

The x^3 has the coefficient of 12

The resulting ploynomial has a degree of 4

User Iacopo
by
4.8k points